A criação de animações de mecanismos de reações orgânicas como método de ensino - Conceição, Lucas Sobral Marques da; Mendonça, Marcia Vivancos; Mendonça, Marcia Vivancos; Farah, João Pedro Simon; Farah, João Pedro Simon (Revista de Graduação USP, 2017)
Scientific visualization is a well-known technique to graphically illustrate data from scientific work. The creation of dramatic images and their animation which combines science and the visual art can inspire attention and curiosity for complex subjects. Over the time we developed a model to study chemical reaction mechanism using scientific visualization for high school level students. The demonstration of a real time in vitro experiment is followed by a discussion of how, when and why atoms are rearranged in the new molecules of the products. A scientific question is stated, and motivation for answering emerges from the creation of a 3D animation based on the changes of electronic density molecular surfaces, going from reactants to products. The question is presented in the context of a scientific problem and not as an answer to specific mechanism proposals. We consider questions raised by well-established knowledge in the literature and use it to address questions suggested by the observation of both in vitro and in silico processes. The animation itself is pure magic and subjects such as kinetics and thermodynamics of chemical reactions are addressed in a gradual manner. One semester of regular activity can produce satisfactory results, very independently of previous knowledge in that matter. This model allows comprehensive contact with some basic principles of quantum chemistry and molecular modeling techniques. One of the main goals achieved were to develop some scientific feeling and a kind of intuition based on good sense, very useful in the scientific work. The other observations are: 1) the importance of real experiments no mater its complexity degree; 2) visualization of abstract concepts is always better than mathematics only; 3) there are no contraindications.